Modified variable neighborhood search algorithm for maximum power point tracking in PV systems under partial shading conditions - Hazem W. Marar; Rosana W. Marar (Universitas Ahmad Dahlan, 2022)
Photovoltaic (PV) systems are being increasingly popular for power generation from solar radiation as the usage of renewable energy grows. To improve the efficiency, the system should operate at its the maximum power point. Hence, several algorithms have been developed for this purpose. Continuous tracking for the maximum power point often leads to heavy energy loss. Furthermore, partial shading can dramatically lower the performance of the system. A modified variable neighborhood search algorithm is proposed resulting zero oscillations around the operating point. A set of variables are used to improve the system’s configurability in various atmospheric and geographical conditions. Simulation result proves the operation of the proposed algorithm, its accuracy, and its fast response time.